2014
DOI: 10.1371/journal.pone.0102010
|View full text |Cite|
|
Sign up to set email alerts
|

EPO Promotes Bone Repair through Enhanced Cartilaginous Callus Formation and Angiogenesis

Abstract: Erythropoietin (EPO)/erythropoietin receptor (EPOR) signaling is involved in the development and regeneration of several non-hematopoietic tissues including the skeleton. EPO is identified as a downstream target of the hypoxia inducible factor-α (HIF-α) pathway. It is shown that EPO exerts a positive role in bone repair, however, the underlying cellular and molecular mechanisms remain unclear. In the present study we show that EPO and EPOR are expressed in the proliferating, pre-hypertrophic and hypertrophic z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 59 publications
2
48
0
Order By: Relevance
“…Many of the studies described above reported that EPO-mediated bone formation and healing was associated with increased vascular density and angiogenesis. EPO treatment was shown to increase endothelial sprouting from metatarsal bones of E17.5 embryos, induce the vasculature in bone in vivo, as well as stimulate endothelial cell proliferation in vitro [3336]. These findings are consistent with previous reports that EPO signaling regulates angiogenesis [27].…”
Section: Epo and Bone Formationsupporting
confidence: 90%
See 1 more Smart Citation
“…Many of the studies described above reported that EPO-mediated bone formation and healing was associated with increased vascular density and angiogenesis. EPO treatment was shown to increase endothelial sprouting from metatarsal bones of E17.5 embryos, induce the vasculature in bone in vivo, as well as stimulate endothelial cell proliferation in vitro [3336]. These findings are consistent with previous reports that EPO signaling regulates angiogenesis [27].…”
Section: Epo and Bone Formationsupporting
confidence: 90%
“…Subsequent studies demonstrated that EPO alone is sufficient to increase bone volume and repair. EPO treatment enhanced both bone volume and biomechanical properties in multiple murine femoral fracture repair models [3335]. Similarly, EPO stimulated BMP2-induced bone formation in cranial defect and scaffold models [36, 37].…”
Section: Epo and Bone Formationmentioning
confidence: 99%
“…As well, PDGF is highly expressed by platelets, as are other signaling proteins, such as thrombospondin-1, both will be discussed in the next section. While RBC are not signaling cells, it is notable that Erythropoietin (EPO) that is necessary for RBC production has been shown in a number of studies to positively influence bone regeneration (18,19). formation), must be recruited to the provisional inflammatory callus ( Figure 1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…LOXL2 was shown to be important in sprouting angiogenesis [15], a process important in endochondral bone formation and bone healing [79]. Hypoxia induces a variety of gene expressions in endothelial cells to induce angiogenesis.…”
Section: Lysyl Oxidase Familymentioning
confidence: 99%